How deliberate organizational learning contributes to the attainment of dynamic capabilities? A case Study of AstraZeneca Pharmaceuticals - Muaid, Reem (2017)
ABSTRACT – I This paper draws on the dynamic capabilities and organizational learning to provide a comprehensive model to examine and evaluate the constituents of both concepts and unsheathe new insights necessary to sustain organizational successful performance in a dynamic, unstable economy. Dynamic capabilities defined as the ability to create, deploy and renew the organization’s resource base in response to the changing environment. Three main dynamic capabilities were addressed; sensing, seizing and reconfiguration based on the work of Teece (2007). Learning mechanism are critical to the development of dynamic capabilities. Learning mechanisms defined as routinized activities directed at the development of operational routines based on the work of Zollo & Winter (2002). The purpose of this study to explore and establish the nature of the interactive relationship between organizational learning and dynamic capabilities. This research employed a case study of a pharmaceutical company, through semi-structured interviews as the main data collection tool using a qualitative approach. The argument is made that there is a dynamic and 2-way relationship between dynamic capabilities and organizational learning. To exploit the benefit of dynamic capabilities, we argue that learning mechanisms must be designed to address each of the dynamic capabilities. The framework developed in this research enables organizational learning output to be fully captured and incorporated back into the dynamic capabilities, at the same time, addressing the input of dynamic capabilities back into the organizational learning to improve learning mechanisms and enrich the knowledge asset of the firm. The thesis concludes with recommendations for organizations in designing organizational learning mechanisms.